Reduction of a Tetrafluoroterephthalonitrile‐β‐Cyclodextrin Polymer to Remove Anionic Micropollutants and Perfluorinated Alkyl Substances from Water. Issue 35 (24th July 2019) - Klemes, Max J.; Ling, Yuhan; Ching, Casey; Wu, Congyue; Xiao, Leilei; Helbling, Damian E.; Dichtel, William R.
Abstract: Organic micropollutants (MPs) are anthropogenic substances that contaminate water resources at trace concentrations. Many MPs, including per‐ and polyfluorinated alkyl substances (PFASs), have come under increased scrutiny because of their environmental persistence and association with various health problems. A β‐cyclodextrin polymer linked with tetrafluoroterephthalonitrile (TFN‐CDP) has high affinity for cationic and many neutral MPs from contaminated water because of anionic groups incorporated during the polymerization. But TFN‐CDP does not bind many anionic MPs strongly, including anionic PFASs. To address this shortcoming, we reduced the nitrile groups in TFN‐CDP to primary amines, which reverses its affinity towards charged MPs. TFN‐CDP exhibits adsorption distribution coefficients (log  K D values) of 2–3 for cationic MPs and −0.5–1.5 for anionic MPs, whereas the reduced TFN‐CDP exhibits log  K D values of −0.5–1.5 for cationic MPs and 2–4 for anionic MPs, with especially high affinity towards anionic PFASs. Kinetic studies of the removal of 10 anionic PFASs at environmentally relevant concentrations showed 80–98 % removal of all contaminants after 30 min and was superior to commercial granular activated carbon. These findings demonstrate the scope and tunability of CD‐based adsorbents derived from a single polymerization and the promise of novel adsorbents constructed from molecular receptors. Abstract : Organic micropollutants (MPs), including per‐ and polyfluorinated alkyl substances (PFASs), contaminate water resources at trace concentrations. A β‐cyclodextrin polymer linked with tetrafluoroterephthalonitrile (TFN‐CDP) has high affinity for cationic and many neutral MPs but does not bind the anionic PFASs strongly. To address this shortcoming, the nitrile groups in TFN‐CDP were reduced to primary amines, providing a material that removes anionic PFASs.